2021
DOI: 10.1093/eurjcn/zvab001
|View full text |Cite
|
Sign up to set email alerts
|

Motivational interviewing in a nurse-led outpatient clinic to support lifestyle behaviour change after admission to a stroke unit: a randomized controlled trial

Abstract: Aims Modification of health behaviour is an important part of stroke risk management. However, the majority of people with cardiovascular disease fail to sustain lifestyle modification in the long term. We aimed to evaluate the effectiveness of motivational interviewing to encourage lifestyle behaviour changes after transient ischaemic attack (TIA) or minor ischaemic stroke. Methods and results  We performed a randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…An increasing body of research has repeatedly indicated that physical activity interventions led by nurses may be effective for increasing physical activity in primary care settings (Olsen et al, 2018; Richards & Cai, 2016). Similarly, nurses have been shown to be valuable in hospital-based physical activity interventions and rehabilitation, including in patients undergoing hemodialysis (Perez-Dominguez et al, 2021) and those admitted to a stroke unit (Brouwer-Goossensen et al, 2021). More specifically, one of the most important roles that nurses can offer is physical activity counselling, specifically by providing support and motivation to clients (Richards & Cai, 2016).…”
Section: Background and Purposementioning
confidence: 99%
“…An increasing body of research has repeatedly indicated that physical activity interventions led by nurses may be effective for increasing physical activity in primary care settings (Olsen et al, 2018; Richards & Cai, 2016). Similarly, nurses have been shown to be valuable in hospital-based physical activity interventions and rehabilitation, including in patients undergoing hemodialysis (Perez-Dominguez et al, 2021) and those admitted to a stroke unit (Brouwer-Goossensen et al, 2021). More specifically, one of the most important roles that nurses can offer is physical activity counselling, specifically by providing support and motivation to clients (Richards & Cai, 2016).…”
Section: Background and Purposementioning
confidence: 99%
“… 68 The longest total intervention duration was a multicomponent support programme incorporating motivational interviewing, this involved eight face-to-face appointments and continued up to 24 months poststroke. 55 Brief interventions included 15 min motivational interviewing sessions by an experienced nurse practitioner at 4, 8 and 12 weeks 41 and daily mobile phone messages for 3 months. 42 The e-health intervention provided constant monitoring for 14 days.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven of the studies mentioned supporting self-management. 41 47 53 55 56 58–60 62 66 70 One study included carers in its outcome measures 66 and no fidelity testing was described. All intervention components are presented in online supplemental file 3 .…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in 14 citations that met criteria for inclusion in this scoping review. [23][24][25][26][27][28][29][30][31][32][33][34][35][36] The flow of citations through identification to final article selection is illustrated in Figure 1 Age, sex, and race. The average age of participants across studies was 64 (range: 50-71) years; the average age of participants was 50-59 years in 3 studies, 60-69 years in ten studies, and 70-71 years in 1 study.…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in 14 citations that met criteria for inclusion in this scoping review. 23-36 The flow of citations through identification to final article selection is illustrated in Figure 1. The 14 included articles and abstracted study characteristics, intervention characteristics, dietary measures, and dietary outcomes are presented in Table 1 and summarized below.
Figure 1.PRISMA flow diagram.
…”
Section: Resultsmentioning
confidence: 99%